Three seasons of enhanced safety surveillance of a cell culture-based quadrivalent influenza vaccine - Alexander Domnich; Daniela Amicizia; Piero Luigi Lai; Matilde Ogliastro; Maria Piedrahita-Tovar; Andrea Orsi; Giancarlo Icardi; Donatella Panatto (Taylor & Francis Group, 2023)
The objective of this paper is to summarize annual enhanced safety surveillance activity across three seasons (2019/20-2021/22) for cell culture-based quadrivalent influenza vaccine (QIVc; Flucelvax® Tetra) in all age groups. This activity was conducted in primary care setting in Genoa (Italy) during the seasons 2019/20, 2020/21 and 2021/22. All adverse events registered within the first seven days following immunization were analyzed by season, type, age group and seriousness. Over three seasons, 3,603 QIVc exposures were recorded within the enhanced passive safety surveillance activity. No safety signals were identified. The overall reporting rates of individual case safety reports for the seasons 2019/20, 2020/21 and 2021/22 were 1.75%, 0.48% and 0.40%, respectively. The average number of adverse events per individual case safety report was similar (range 3.3-3.8 adverse events per case report) across the three seasons. Most adverse events were reactogenic in nature. The rate of adverse events was similarly low in all age groups. Enhanced passive safety surveillance activity is a feasible approach for the post-marketing monitoring of seasonal influenza vaccines. Within its limitations, results of this study support the favorable safety profile of QIVc. These safety data could further bolster public trust in influenza vaccines with the goal to increase vaccination uptake in all target groups.